Isolation and Molecular Identification of Endophytic Mold Schizophillum commune in Red Dahlia (Dahlia sp. L) Tuber as Producing Inulinases - Sunarti, Sunarti; Ginting, Chrismis Novalinda; Ginting, Sahna Ferdinand (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Dahlia tuber as the source of isolates in endophytic mold produces Inulinases. Inulinase is used in industry to produce inulin to become fructose through an enzymatic reaction. Fructose from natural substances constitutes low calories used as diet in diabetes mellitus type 2 patients. An important phase is done obtain the inulinase enzyme through mold isolation. AIM: The objective of this research was to isolate and identify the molecular of endophytic mold from red dahlia tuber which had the optimum inulinase activity. METHODS: Mold isolation was done through the stage of surface sterilization and purification. Mold isolation which had the highest inulinase activity was identified in a molecular using the polymerase chain reaction technique with the Internal transcribed spacers ITS region. DNA amplification used primer ITS 1 and ITS 4. RESULTS: The result of the study showed that there was five-mold isolation with the result of screening high inulinase activity found in UD3 (++), UD4 (++), and UD5 (+++), the value of inulinase enzyme activity of UD3 was 0.582716049, UD4 was 0.330864198, and UD5 was 0.685185185. The result of identifying UD5 molecular in eight DNA tapes was successfully amplified with 660 pb. The result of identifying molecular based on BLAST analysis found Schizophillum commune species CONCLUSION: It was found that the highest inulinase activity was the species S. commune, which added new variants of inulinase enzyme from red dahlia tuber which could be used by industry to yield fructose through an enzymatic reaction.